Advancing Lifelong Learning in the Digital Age: A Narrative Review of Singapore’s SkillsFuture Programme - Zhi Yong Lim; Jun Hong Yap; Joel Weijia Lai; Intan Azura Mokhtar; Darren J. Yeo; Kang Hao Cheong (Social Sciences, 2024)
Amidst the fourth industrial revolution, marked by swift technological advancements and changing economic environments, lifelong learning has risen as an essential cornerstone for developing people and society. Adult education, with a particular focus on skills learning, is vital in equipping individuals with the necessary competencies to navigate the dynamic demands of the modern workforce. This paper provides a qualitative analysis and commentary on the case study of Singapore’s SkillsFuture movement, an exemplary national initiative to promote skills learning among adults. Intending to reach a wide audience in educational science, we investigate the effectiveness and impact of this comprehensive programme and its implications for other countries. This article contributes to educational science and policy development by illustrating the importance of investing in adult education and skills development. By comprehensively studying the SkillsFuture experience, we offer valuable insights into establishing effective and inclusive lifelong learning ecosystems to foster a culture of continuous learning, equipping individuals to adapt and thrive in a volatile, uncertain, complex, and ambiguous global landscape.